1976
DOI: 10.1113/jphysiol.1976.sp011541
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of citrate into milk.

Abstract: SUMMARY1. The time course of changes in specific activities of citrate, lactose and fatty acids in milk during frequent milking, following the ixv. administration of labelled glucose, acetate and chylomicrons in goats has been studied. Peak specific activities of lactose and citrate in milk were reached at 2-3 hr, while peak specific activities of fatty acids were reached at 5-7 hr.2. Following short I.A. infusions of 24Na, 3"Cl and 42K, peak specific activities in milk were reached in 1 hr or less.3. The mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 24 publications
2
60
1
Order By: Relevance
“…While substantial dilution of milk in vivo with isosmotic sucrose or lactose solutions does not lead to the changes observed with citrate included (Linzell et al 1976;Peaker, 1977;Neville & Peaker, 1979), it seems likely that Ca2+ could be replenished by re-equilibration of reactions between Ca2±, calciocitrate and protein-associated calcium under these circumstances. If Ca2+ in milk is important for epithelial integrity, the question arises of whether calcium movements or binding control milk composition when the proposed epithelial paracellular pathway through leaky junctions (see Linzell & Peaker, 1971;Peaker, 1978) opens or closes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While substantial dilution of milk in vivo with isosmotic sucrose or lactose solutions does not lead to the changes observed with citrate included (Linzell et al 1976;Peaker, 1977;Neville & Peaker, 1979), it seems likely that Ca2+ could be replenished by re-equilibration of reactions between Ca2±, calciocitrate and protein-associated calcium under these circumstances. If Ca2+ in milk is important for epithelial integrity, the question arises of whether calcium movements or binding control milk composition when the proposed epithelial paracellular pathway through leaky junctions (see Linzell & Peaker, 1971;Peaker, 1978) opens or closes.…”
Section: Discussionmentioning
confidence: 99%
“…2). However, it is difficult to interpret changes at this milking because of four complicating factors: (i) the presence of the additional volume of liquid in the gland would tend to depress concentrations by a dilution effect; (ii) the presence of additional Na in the citrate-sucrose solution, although when this is allowed for the Na concentration was still increased; (iii) the tendency for Na, K and Cl to pass into the diluted milk from the cell as a result of altering the concentration gradients (Linzell, Mepham & Peaker, 1976); (iv) the additional citrate could affect anion movements by a Donnan or other effect. Therefore, interpretation of the effects of the solution is not based on changes at this milking.…”
Section: Milk Yield and Composition Effects Of Citratementioning
confidence: 99%
“…However, earlier studies showed that the secretion of fat, protein, Ca and citrate continues when the rate of lactose and water secretion is very low (Hardwick et al 1961;). Since there is evidence that protein (see , Ca (Baumrucker & Keenan, 1975) and citrate (Linzell, Mepham & Peaker, 1976) are secreted, like lactose, by exocytosis of vesicles arising from the Golgi apparatus, it is clear that the normal secretary processes of exocytosis and lipid droplet extrusion continue in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In all cases sterile 300 mM-sucrose solution at approximately 37 0C was pumped into the cistern via a catheter in the teat canal. The validity of this procedure in terms of failure to induce osmotic water movements is discussed by Linzell, Mepham & Peaker (1976) and Peaker (1977).…”
Section: Introductionmentioning
confidence: 99%